Behaviour of environment friendly green concrete beams using fly ash and furnace slag under cyclic loading. (10th April 2019) - Annamalai, S.; Thirugnanasambandam, S.; Muthumani, K.
This paper investigates an alternative binder to Portland cement binder which is very friendly to environment as Portland cement emits 0.8 ton to 1.0 ton of greenhouse gas (CO2 ) during the production of 1.0 ton of cement. To test the suitability of GPC against RCC for structural applications, four beams of size 125 mm × 250 mm × 3, 200 mm were cast. Two for reinforced cement concrete (RCC) which act as control beams (CB) and two for GPC. The beams were tested up to failure under monotonic as well as cyclic loading in a reaction frame under displacement control to study the flexural cyclic behaviour.